Review on reverse electrodialysis process-a pioneering technology for energy generation by salinity gradient - Gül, Taha Furkan; Akalın, Minel; Dönmezler, Eda Nur; Bolat, Ahmet; Cihanoğlu, Aydın; Güler, Enver; Kabay, Nalan (Frontiers in Membrane Science and Technology, 2024)
Blue energy obtained by salinity gradient can be generated by mixing two saline solutions having different salt concentrations. According to researchers working in this area, about 80% of the current global electricity demand could potentially be covered by this energy source. There are basically two membrane technologies so-called pressure-retarded osmosis (PRO) and reverse electrodialysis (RED) that are capable to generate electrical energy from salinity gradient. The pressure driven PRO process is more suitable for energy generation from highly concentrated brines. However, RED is more favorable for power generation by mixing seawater and river water.In RED process, ion exchange membranes (IEMs) placed between two electrodes in a stack were employed for transport of ions. Thus, an electrical current is obtained at the electrodes by electron transport through redox reactions. This review gives an overview of RED as a pioneering technology for salinity gradient energy (SGE) generation. The review summarizes the recent improvements of IEMs employed for RED studies, membrane fouling and RED stack design.